The conquest of happiness - Russell Bertrand
"The conquest of Happiness, a primer of self -regeneration, is a most excellent book. This manual of systematized common sense, sane and forthright, should be read by every parent, teacher, mister, and Congressman in the land:" Atlantic Monthly. "Since happiness is the goal of everybody nd since almost nobody knows the road to it, this book is bound to become the preocupation of many who believe in happiness, and hope that it is attainable ...Finely straight, beutifully simple, immediate to everyone in its outlook and suggestion. Our part is not only to read, but to get busy as well." The books of Bertrand Russell are a modern substitute for the Bible."